Experiential Marketing and Customer Satisfaction: A Study on the Restaurant Industry of Bangladesh - Amin, Sanjida; Tarun, Md Touhiduzzaman (Asian Business Review, 2019)
This research report aims to explore the factors of experiential marketing to determine their impact on customer satisfaction in the restaurant industry of Bangladesh. Three Hypotheses were developed by the researcher to identify the factors of experiential marketing and their impact on overall customer satisfaction. The research study is conducted by a quantitative research approach to get the insights and understandings of experiential marketing and to figure out the strength of association between dependent and independent variables. Empirical data was gathered by the author himself from 150 respondents who were present in the restaurants at that time through the self-administered survey questionnaire. By applying a convenience sampling method, the researcher collected data from the respondents under different clusters. Researcher used regression and factor analysis to analyze the statistical data through the SPSS software. The research concluded with the significant positive relationships of sense experience, feel experience, and think experience with customer satisfaction. The outcome of the study will assist managers, restaurant owners and, decision makers with the insights and understanding of experiential marketing and its influence on customer satisfaction.